(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Placenta previa is a major obstetric complication in which the placenta is implanted in the lower uterine segment, partially or completely covering the internal cervical os, leading to antepartum hemorrhage, operative delivery, and increased maternal and neonatal morbidity. Its incidence has gained importance with rising cesarean section rates and improved ultrasonographic diagnosis. Aim & Objective: To study the prevalence of placenta previa, evaluate maternal and fetal outcomes, and identify associated risk factors. Materials & Methods: This hospital-based observational study was conducted in the Department of Obstetrics and Gynaecology, MCH, KIMS Koppal, from June 2024 to May 2025. Pregnant women diagnosed with placenta previa after 28 weeks of gestation, either clinically or by ultrasonography, were included. Detailed history, clinical examination, investigations, intraoperative findings, maternal complications, and neonatal outcomes were recorded and analyzed. Results: A total of 38 cases were studied. Most women were aged 31 to 35 years (47.0%) and multiparous, with para 2 to 4 constituting 65.7%. Previous cesarean section was present in 75.0% cases. Cesarean delivery was performed in 78.94%. Maternal morbidity included blood transfusion (47.3%), uterine artery ligation (26.3%), postpartum hemorrhage (21.05%), ICU admission (7.89%), and cesarean hysterectomy (5.26%), with no maternal mortality. Neonatal outcomes showed birth weight ≥2.5 kg in 70.0%, APGAR score ≥6 in 72.0%, NICU admission in 28.9%, and perinatal death in 10.05%. Advanced maternal age and multiparity were prominent associated factors. Conclusion: Placenta previa remains a significant cause of maternal and perinatal morbidity. Early diagnosis, timely referral, blood bank preparedness, and multidisciplinary management are essential for improving fetomaternal outcome and reducing preventable complications in high-risk pregnancies managed at tertiary care centres overall.